Influence of Sea Surface Temperature in the Tropics on the Antarctic Sea Ice during Global Warming - Genrikh Alekseev; Anastasiia Vyazilova; Alexander Smirnov (Journal of Marine Science and Engineering, 2022)
Sea ice extent in the Antarctica, unlike in the Arctic, did not show a decrease until 2016 under observed global warming. The aim of the study is to explain this climatic phenomenon based on the idea of joint dynamics of the Southern Ocean oceanic structures—the Antarctic polar front, the boundary of the maximum sea ice extent and atmospheric structures—Intratropical Convection Zone (ITCZ) and the Hadley circulation. ERA5 reanalysis and HadISST data were used as well as the sea ice database for the period 1979–2021. The effect of SST at low latitudes of the North Atlantic on the position of the Antarctic polar front and the maximum sea ice extent has been established. The SST in the same area of the North Atlantic has an opposite effect on the sea ice extent in the Arctic. The impact of the SST on the sea ice is mediated through the ITCZ and the Hadley circulation. The obtained results confirmed the key role of the SST at the low latitudes of the North Atlantic in the development of multidirectional trends in changes in the Arctic and the Antarctic ice cover in 1979–2016.